Testing the Waters: Plant Working and Seafaring in Pleistocene Wallacea - Fuentes, Riczar (Archīum Ateneo, 2025)
While the presence of fossils and artefacts provide ample evidence that early modern humans were able to cross the open sea, the very circumstances of why and how they moved into and across Island Southeast Asia (ISEA), and particularly the Wallacean region, remain to be addressed. In this paper we explore the connection between traces of plant working and boatbuilding in coastal sites during the Pleistocene to infer how prehistoric people migrated to and through the region. Artefactual evidence of watercrafts is missing in the archaeological record of the region as the maritime technology employed was most likely dominantly made of plants and its components have decayed over time. Nevertheless, various seacraft designs have been proposed for reaching the isolated island of the Wallacean archipelago. In theoretical and experimental considerations, the focus has usually been on bamboo rafts as the main seacraft design, probably inspired by the so-called ‘bamboo hypothesis’. The identification of boat building materials through direct or indirect evidence is vital in understanding movements across and within island environments. In this paper, we argue that experimentation and traceology can address questions on prehistoric sea crossings, with a focus on the connection between traces of prehistoric plant processing and seacrafts that were potentially used in ISEA – arguably an indication of behavioural modernity. We highlight the role of plant working, specifically the extraction of fibres, for making cord work and related objects in ISEA during the Late Pleistocene and the possibility of identifying such activities through use-wear and residue analysis. Overall, we contextualise the current state of research on direct and indirect pieces of evidence for prehistoric plant technology in Wallacea in relation to seafaring, island connections, and maritime-based subsistence.